A qualitative study of mentors’ perceptions and experiences of a near-peer mentoring program for medical students - Pölczman, Lea; Jámbor, Márk; Győrffy, Zsuzsa; Purebl, György; Végh, András; Girasek, Edmond (Frontiers in Education, 2024)
During their academic studies, medical students may encounter a variety of challenging situations. It is no wonder that they have a higher prevalence of poor mental health than the general population. Mentoring programs have proven useful in promoting mental health in medical education. The study aimed to explore the perceptions and experiences of medical students as mentors in a near-peer mentoring program. Methods: A qualitative study was carried out between March and April 2022 at Semmelweis University in Budapest, Hungary. Five focus group discussions (FGDs) included 26 medical students who were enrolled as mentors in the mentoring program. The recordings were transcribed verbatim and anonymized. An deductive and semantic approach was adopted, and the data were analyzed with thematic analysis. Results: Three major themes were identified: professional and personal growth and reflections on the mentoring experience. Mentors reported growth in social and practical problem-solving skills, self-confidence, psychosocial benefits, and both personal and professional development. The program had a great impact on students' sense of self-efficacy, self-awareness, perception of their competencies, and adherence to their boundaries. Discussion: In conclusion, the mentors strongly emphasized the professional and psychosocial benefits they perceived while participating in the mentoring program. Therefore, the experiences obtained during the mentoring are important milestones. Mentoring programs could greatly improve students both personally and professionally so that later, they will be the best possible professionals in the field of health care.